Leaders in the Historical Study of American Education - Urban, Wayne J.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
This volume consists of twenty six autobiographical essays by leading historians of American education which document the enormous variety of paths taken to get into this field. A companion to earlier volumes on philosophy of education and curriculum studies, the historians in this volume reflect a wide variety of interests that underlay accomplishment in this scholarly field. They come from diverse backgrounds that have animated their scholarly careers in compelling ways. Readers in any variety of educational or historical study should learn from this volume how unplanned careers can still result in highly successful sets of accomplishments. That realization is a tribute both to the individual contributors and to the great attractiveness of educational history to committed scholars of various backgrounds and orientations.
Keywords: Education; Education; Administration, Organization and Leadership